Adaptation of the PG-13-R Instrument to Measure Prolonged Grief Disorder in Adolescents - Muhtadi, Hasna Fathinah; Ahman, Ahman (citeus, 2025)
Grief due to the loss of a loved one is a normal reaction that can be experienced by teenagers, but if it interferes with daily life and lasts for a long time, this condition can develop into a prolonged grief disorder. The PG-13-R instrument was introduced by Holly Prigerson, designed to measure prolonged grief disorder. Research is needed to confirm the psychometric performance of the PG-13-R in samples with broader ethnicities. This research involved 242 students at SMKN 1 Tasikmalaya, Indonesia using a descriptive quantitative approach. This research aims to measure and describe the characteristics of the validity and reliability of the Indonesian version of the PG-13-R instrument for adolescents who have experienced loss. The results of the validity and reliability test show that the Indonesian version of the PG-13-R instrument has a good level of validity and reliability, with all items declared valid and a high reliability value (Cronbach's alpha = 0.888). Thus, the adapted PG-13-R instrument can be indicated as a valid and reliable measuring tool for identifying prolonged grief disorders in adolescents in Indonesia.